Post-pandemic social cohesiveness in English language learning: Actors’ capacity transformation - Nur Rahmiani; Pratya Binmudnee; Sam Ayo Ojurongbe (UPT Bahasa Universitas Tanjungpura, 2022)
This study explores forms of social cohesiveness, the factors that encourage the realization of social cohesiveness, and the impact of social cohesiveness on actors involved in learning English after the Covid-19 pandemic. As the primary research data, the research employs the qualitative descriptive research method based on interviews with ten students from rural areas in West Kalimantan, Indonesia. For secondary data, the authors employed theoretical studies and previous research results from books, articles, and other scientific publications. The findings of this study suggest that there has been a positive interaction where teachers and students strengthen each other in the English learning process after the Covid-19 pandemic. This interaction is seen to foster social cohesiveness, which can be a teaching innovation for achieving learning targets. Social cohesiveness becomes a part of the process of transforming the capacity of each actor and is a form of social resilience in learning English after the Covid-19 pandemic. The findings implicate the developing humanistic innovations of English language teaching in a rural setting and recognize the peculiar limitations of the setting.